IMPLEMENTASI TOTAL QUALITY MANAGEMENT UNTUK MENINGKATKAN KINERJA PERUSAHAAN - MOH. NASIKH (Jurnal Akademika, 2021)
I am very interested in studying this journal to describe about Implementation Total Quality Management (TQM) to Increasing Company Performance, and discussing about how to market our products or services to be accepted by consumers (customer focus). For the time being, I am very interested to discuss some ways that can be used to multiply or increase our sales units or our values or profit by using TQM or planning, controlling (inspection) and quality assurance and products or services improvement from raw material (input) until finished goods (output), and finally can be marketed to consumers (customers) or accepted by them with continuously repurchasing and also how to promote our products or services to them by using total quality management (TQM) or integrated quality management. Beside that, I am also interested in discussing momentary issues, such as: cycle of product development, safety of products or services, the products or servives that not get along with prime standards, correlation with some supliers, and about education and training for employees, also issues of ethics. So, in the prospect, our products or services are able to increase values and units or to overcome the market-share, because they are so very competitive ones (market-based competition) and very sustainable thing. Keywords: Total Quality Management (TQM), Management Performance